How America Compares - Tiffen, Rodney. author. aut Link
XXI, 192 p. 1 illus.
Keywords: This book is a reference work with an encyclopedic range, offering contemporary and systematic comparisons between the United States and 17 other economically advanced, stable liberal democracies, as well as some more global comparisons. It offers international data on as many aspects of social life as possible, from taxation to traffic accidents, homicide rates to health expenditure, and interest rates to internet usage. Wherever possible it offers not only the most recent available data but also trends over decades. The discussion focuses on changes over time and comparisons between countries. Sometimes the contrasts are striking; sometimes the commonalities are more instructive. Often national political debates are conducted in a vacuum, and examining comparative data on policies, performance and prospects can give a better perspective. .